Intercultural competence of Chinese students abroad: An investigation under Sino-foreign Cooperative Education Programs - Pei Yang; Xiangge Zhao; Xinxin Zhang; Anran Li (PLoS ONE, 2025)
The rapid growth of Sino-Foreign Cooperative Education Programs highlights the critical role of intercultural competence (IC) for Chinese students studying abroad. While extensive research exists on domestic contexts, empirical studies on Chinese students’ experiences at foreign partner institutions remain scarce. This study addresses this gap by examining the intercultural competence of Chinese students in these programs and identifying key factors influencing their development. Using a mixed-methods approach, the study surveyed 130 Chinese students in Ireland and conducted WeChat video interviews with 16 participants. The results indicate that Chinese students generally exhibit moderately high levels of IC. Language proficiency, intercultural training, and intercultural contact experiences were significantly and positively associated with IC, while gender showed no significant correlation. These findings highlight the complex interplay of factors shaping intercultural competence in international education. The study offers valuable insights for educators and policymakers to improve intercultural training and support in Sino-Foreign Cooperative Education Programs. It also fills a key research gap by providing empirical evidence on Chinese students’ intercultural experiences abroad, laying the groundwork for future research and practical improvements.